2022
DOI: 10.1002/pul2.12001
|View full text |Cite
|
Sign up to set email alerts
|

Disease characteristics and clinical outcome over two decades from the Swiss pulmonary hypertension registry

Abstract: Pulmonary hypertension (PH), especially pulmonary arterial and chronic thromboembolic pulmonary hypertension (PAH/CTEPH), are rare and progressive conditions. Despite recent advances in treatment and prognosis, PH is still associated with impaired quality of life and survival. Long‐term PH‐registry data provide information on the changing PH‐epidemiology and may help to direct resources to patient's needs. This retrospective analysis of the Swiss Pulmonary Hypertension Registry includes patients newly diagnose… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(77 reference statements)
1
7
0
Order By: Relevance
“…The 1-year survival estimate observed here for incident patients (88%) is similar to that seen for incident patients in disease registries (86%–95%) [ 3 – 5 , 11 , 12 , 14 , 19 ]. In the past decade, analyses from national registries [ 15 , 25 ] have shown that populations of incident patients tend to have worse survival than prevalent patients, which could reflect a survival bias among the prevalent patients [ 26 ].…”
Section: Discussionsupporting
confidence: 80%
“…The 1-year survival estimate observed here for incident patients (88%) is similar to that seen for incident patients in disease registries (86%–95%) [ 3 – 5 , 11 , 12 , 14 , 19 ]. In the past decade, analyses from national registries [ 15 , 25 ] have shown that populations of incident patients tend to have worse survival than prevalent patients, which could reflect a survival bias among the prevalent patients [ 26 ].…”
Section: Discussionsupporting
confidence: 80%
“…This finding is consistent with not only long-term follow-up data from patients with PH due to valvular heart disease, but also registry data from patients with PAH, including the Swiss PH Registry. 4 , 10 Furthermore, a female predominance in patients with PH due to heart failure with preserved ejection fraction has been previously reported. 11 The impact of specific aetiologies of chronic LHD leading to CpcPH should be further investigated.…”
Section: Discussionmentioning
confidence: 91%
“…The design of the Swiss PH Registry has been described previously. 4–6 All participants gave written informed consent to have their data registered and used for research. The clarification of responsibility conducted by the Cantonal Ethics Review Board concluded that no further ethical approval is needed (BASEC-No.…”
Section: Methodsmentioning
confidence: 99%
“…The main findings are mainly driven by patients ≥50 years, which is due to the large sample size in this age group (119 versus 24). The haemodynamic limitations of included patients were generally slightly milder compared with the latest Swiss PH registry data, which revealed an mPAP of 41±11 mmHg along with a PVR of 7±4 WU for the years 2016–2019 [ 16 ]. This was most probably because we chose to study patients with relatively mild disease who were able to perform exercise RHC.…”
Section: Discussionmentioning
confidence: 99%